The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.jinorgbio.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A novel binuclear hydrazone-based Cd(II) complex is a strong pro-apoptotic inducer with significant activity against 2D and 3D pancreatic cancer stem cells

Abstract: A novel binuclear Cd complex (1) with hydrazone-based ligand was prepared and characterized by spectroscopy and single crystal X-ray diffraction techniques. Complex 1 reveals a strong pro-apoptotic activity in both human, mammary adenocarcinoma cells (MCF-7) and pancreatic AsPC-1 cancer stem cells (CSCs). While apoptosis undergoes mostly caspase-independent, 1 stimulates the activation of intrinsic pathway with noteworthy down regulation of caspase-8 activity in respect to non-treated controls. Distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 149 publications
0
4
0
Order By: Relevance
“…It has been shown that some of them directly target the DNA chain and inhibit of incorporation of 3H-thymidine into DNA. 14 Furthermore, they can target DNA non-covalently by groove binding, 15 intercalation, [16][17][18] or combinations of these two modes. 19 In addition to DNA, they can also be directed at other protein targets.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that some of them directly target the DNA chain and inhibit of incorporation of 3H-thymidine into DNA. 14 Furthermore, they can target DNA non-covalently by groove binding, 15 intercalation, [16][17][18] or combinations of these two modes. 19 In addition to DNA, they can also be directed at other protein targets.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Other transition metal complexes have also been synthesized and investigated with significant biological activity. [8][9][10] The biological activity of cadmium complexes has not been further investigated as it is well known that Cd has great toxicity to the human body and metabolizes slowly in the human body. However, it has been reported that the toxicity of Cd is comparable to the toxicity of noble metals, and metal toxicity is not a constant property and depends on many factors like the presence of appropriate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…They show potent anticancer activity and can kill cancer cells via programmed cell death apoptosis. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%